Sistemas de liberação controlada de quitosana contendo antigeno capsular Vi de Salmonella Typhi - SILVA, Raimundo Lopes da (Universidade Federal do Pará, 2014)
The use of the Vi antigen in vaccines is very promising because this provides a high level of immunity in parenteral vaccines. The need for the search for alternatives for administration of vaccines has led to the application of technology controlled release of drugs in the field of immunization. In such controlled delivery systems, the doses are decreased, but the period of immunity increases, extending the amount of antigen released over time. This study aimed to develop and characterize a controlled delivery system containing Vi antigen, using as disseminator polymer chitosan. The techniques of H-1 NMR and infrared spectroscopy showed that the method of extracting the Vi antigen used was qualitatively satisfactory. The characterization of chitosan and nanoparticles by tests thermal analysis showed greater stability of the particles in relation to chitosan, besides increasing the degradation temperature of the nanoparticles increases as the concentration of chitosan. Regarding the zeta potential nanoparticles were all positive charges at pH7.2, while the particles were smaller size as they increased the amount of chitosan in the system. In transmission electron microscopy showed the particles are morphologically homogeneous and spherical. In the adsorption kinetics of antigen contained in solution, suffered a 55% adsorption of the particles of chitosan. With this, we observed that it is possible to create a controlled delivery system involving nanoparticles of chitosan and Vi antigen of Salmonella enterica serotype Typhi.